Development of focal geometry with non-ideal samples - Prokopiou, D. M. (Cranfield University, 2015)
A novel geometry for powder X-ray diffraction (XRD), termed ‘focal construct geometry’ (FCG) is introduced and developed with both non-ideal samples and non-ideal sample conditions. FCG utilises an annular beam that has the unique feature of ‘focusing’ scattering maxima at single loci along a primary axis, hence offering diffraction data of enhanced intensity. This main advantage of FCG can be used within fields in need of rapid material identification, such as security screening in airports. A theoretical comparison between FCG and conventional transmission mode XRD showed that even though FCG suffers from broader diffraction peaks, an alternative approach to FCG data interpretation has the potential to provide narrower scattering maxima than conventional XRD. However, in order to employ this approach, discrimination between converging and diverging FCG scattering maxima is essential. Peak broadening was investigated by altering various aspects of FCG instrumentation components by either pencil beam XRD or FCG, indicating broad diffraction peaks independent of the beam geometry employed. Development of FCG resulted in the successful analysis of non-ideal samples, such as non-crystalline liquid samples, samples exhibiting preferred orientation and samples with large grain size, demonstrating advantages over conventional XRD. Furthermore, ideal samples (in terms of crystallinity, preferred orientation and grain size) were analysed by FCG under non-ideal conditions. This involved randomly orientating a single planar sample with respect to the primary axis, contrary to previous research that present FCG with a single planar sample normal to the primary axis. Sample rotation resulted in FCG scattering maxima with different xyz coordinates depending on the degree, axis and direction of rotation. Moreover, FCG analysis of multiple samples (normal to the primary axis) showed that as with all XRD arrangements, a priori knowledge of the samples’ position along the primary axis is required for effective data analysis. Investigation into the ability of FCG’s annular beam to act as a pre-sample coded aperture demonstrated an alternative method to interpret FCG images by recovering conventional XRD data. Additionally, two novel post-sample encoders (linear wire and Archimedean spiral) were considered. This enabled spatial discrimination of unknown samples along a primary axis and material identification for conventional XRD techniques. Combination of FCG with an absorbing edge post-sample encoder indicated discrimination between converging and diverging FCG scattering maxima. This ability can enable interpretation of single FCG images, as well as depth information of unknown samples within an inspection volume (e.g. airport luggage), hence enabling material identification.
© Cranfield University 2014
Keywords: X-ray diffraction; Aviation security; Detection and detectors